2016
DOI: 10.1007/s00217-015-2614-8
|View full text |Cite
|
Sign up to set email alerts
|

In vitro investigation on the antiglycative and carbonyl trapping activities of hydroxytyrosol

Abstract: Advanced glycation end products (AGEs) are involved in the aging and the development of common chronic diseases. Hydroxytyrosol (HT) and its acetate derivative (HTA) exert a significant inhibitory activity on the formation of fluorescent AGEs in bovine serum albumin glycation model systems induced by methylglyoxal (IC50 value of 0.48 and 0.58 μmol/mL, respectively) and glucose (IC50 2.30 and 2.92 μmol/mL, respectively). Furthermore, HT and HTA showed a relevant carbonyl scavenging capacity toward methylglyoxal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 32 publications
(53 reference statements)
0
16
0
Order By: Relevance
“…Caffeic acid was the most effective molecule exerting a dose-dependent antiglycative effect in both models. An explanation for this effect is related to the MGO-trapping capacity of caffeic acid [ 46 ], which might be exerted via the protection of lysine, arginine, and/or histidine groups [ 47 ]. This mechanism of protection is rather common to ortho-diphenolic compounds with a similar structure to that of caffeic acid and is linked to the antioxidant and chelating activity [ 19 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Caffeic acid was the most effective molecule exerting a dose-dependent antiglycative effect in both models. An explanation for this effect is related to the MGO-trapping capacity of caffeic acid [ 46 ], which might be exerted via the protection of lysine, arginine, and/or histidine groups [ 47 ]. This mechanism of protection is rather common to ortho-diphenolic compounds with a similar structure to that of caffeic acid and is linked to the antioxidant and chelating activity [ 19 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, few studies have established a relationship between health beneficial properties and both antioxidant and antiglycative abilities through the reduction of the reactive dicarbonyl formed by the oxidative stress 27 . In a previous study, Navarro & Morales 24 have been chronically stressed and also stimulated the wound healing of pressure ulcers 40-4137-38 . In the OLEA project, the olive leaf extract has been the target of several investigations where it has been reported that olive leaf extract exerted cytoprotective and anti-inflammatory effects.…”
Section: Dicussionmentioning
confidence: 98%
“…Previous studies have proved that several phenolic compounds present in olive leaves could exert a strong in vitro antiglycative capacity 24,[28][29] MGO-trapping capacity of OLE-B was significantly higher than OLE-A. Further, the αdicarbonyl-trapping capacity of the major phenolic compounds in OLE-A and OLE-B was also evaluated with standards.…”
Section: Inhibition Of the Formation Of Fluorescent Ages In Vitromentioning
confidence: 99%
“…Determination of CML and CEL by LC-MS/MS. CML and CEL were determined as described by Navarro and Morales (2016). LC-MS/MS was coupled to a triple quadrupole and the samples (10 lL) were injected on Hypercarb column (100 mm 2.1 lm, 5 lm, ThermoFisher Scientific).…”
Section: Determination Of Free Fluorescent Agesmentioning
confidence: 99%